KEEFEKTIFAN MEDIA PEMBELAJARAN LOOSE PARTS TERHADAP KARAKTER CINTA LINGKUNGAN DAN KREATIVITAS ANAK USIA DINI - Aprilia Candra Krisnawati; Arri Handayani; Dini Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problems in this research are the lack of children's awareness of environmental cleanliness, there are still children who throw rubbish carelessly, the lack of activities that utilize items in the surrounding environment, the lack of waste sorting facilities, children are bored playing with toys that are frequently used. Children's creative abilities are still low, as can be seen from the fact that learning activities mostly use worksheets, play activities and direct interaction with the surrounding environment are still lacking, children are confused about choosing play activities, play activities are boring. The results of this research show that loose part learning media is effective in cultivating the character of loving the environment and is effective in increasing children's creativity.